Analisis Perbedaan Dan Pendekatan Metode Pembelajaran Dalam Kurikulum Merdeka Dan Kurikulum 13 (K13) Di Sekolah Sma N 1 Dolok Pardamean - Jayanti, Ummi Nur Afinni Dwi; Saragih, Fany Erlangga; Umaroh, Izza Yani; Achyari, Putri Rizq; Amelia, Suhaila Yani; Sinurat, Yulianti Yani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research will make an important contribution to the understanding of these two different curricula in the context of their implementation at the senior high school level. The method used in this research is direct observation, namely coming to school to make observations. The school that the researchers visited for observation was SMA N 1 Dolok Pardamean which is located in Si Pintuangin, Kec. Dolok pardamean Kab. Simalungu, This observation was carried out on the 6th of June 2023. Based on the results of an interview with the principal from SMA, that SMA school started using and implementing the prototype curriculum or which is now renamed the Independent Curriculum in 2021. He also added that not just any school who can apply the prototype curriculum. Schools that can apply the prototype curriculum must be driving schools appointed directly from the government. Then before the preparation of the curriculum was held, teachers and the high school team were required to attend the driving school training which intended that teachers in the driving schools could design and implement the Independent Learning curriculum.